Prognostic Factors and Overall Survival After Pericardiocentesis in Patients With Cancer and Thrombocytopenia - Wilson, Nathaniel R.; Lee, Michelle T.; Gill, Clarence D.; Serauto Canache, Astrid; Donisan, Teodora; Balanescu, Dinu V.; Song, Juhee; Palaskas, Nicolas; Lopez-Mattei, Juan; Cilingiroglu, Mehmet; Marmagkiolis, Konstantinos; Iliescu, Cezar A. (Frontiers in Cardiovascular Medicine, 2021)
Background: Pericardiocentesis is an important diagnostic and therapeutic tool for cancer-associated pericardial effusion. Limited safety and outcomes data exists regarding the management of malignancy-related pericardial effusion in patients with thrombocytopenia. Objectives: Our study aimed to analyze prognostic factors and overall survival (OS) after pericardiocentesis in thrombocytopenic cancer patients. Methods and Results: A retrospective review of 136 thrombocytopenic cancer patients who underwent primary percutaneous pericardiocentesis was performed. Degree of thrombocytopenia was classified by platelet count recorded on day of pericardiocentesis: 75–149 × 103 cells/μL (41%); 50–74 × 103 cells/μL (10%); 25–49 × 103 cells/μL (24%); <25 × 103 cells/μL (25%). Median OS was 2.6 months and median follow-up was 37.4 months. Kaplan-Meier survival analysis showed significant OS differences among thrombocytopenia severity groups (p = 0.023), and worse OS with platelets <100 vs. ≥100 × 103 cells/μL (p = 0.031). By univariate analysis, thrombocytopenia severity was associated with increased risk of death (HR 0.993; 95% CI 0.989–0.997; p = 0.002). Poor prognostic factors for OS were advanced cancer, malignant effusion, elevated international normalized ratio (INR), quantity of platelet transfusions, and platelet transfusion resistance. However, thrombocytopenia severity became insignificant for OS (p = 0.802), after adjusting for advanced cancer and INR. Conclusions: For patients with malignancy-related large pericardial effusion and thrombocytopenia, pericardiocentesis is a feasible intervention and should be considered due to low complication rates. There is no absolute contraindication to pericardiocentesis in case of hemodynamic instability, even with severe thrombocytopenia.